2011
DOI: 10.1186/1756-0500-4-10
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of allele frequencies at TTN g.231054C > T, RPL27A g.3109537C > T and AKIRIN2 c.*188G > A between Japanese Black and four other cattle breeds with differing historical selection for marbling

Abstract: BackgroundMarbling defined by the amount and distribution of intramuscular fat, so-called Shimofuri, is an economically important trait of beef cattle in Japan. Our previous study detected 3 single nucleotide polymorphisms (SNPs), g.231054C > T, g.3109537C > T and c.*188G > A, respectively, in the 5' flanking region of the titin (TTN), the 5' flanking region of the ribosomal protein L27a (RPL27A) and the 3' untranslated region of the akirin 2 genes (AKIRIN2), which have been considered as positional functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…To further analyze the distribution of the well-characterized allele of each SNP in the cattle populations based on the different genetic background, the MGC, MGG, QC, LX, WL and LL of this study as well as the JB, JBR, JSH, HOL, BS and KN [19,[21][22][23] were divided into six groups which including North China (MGC and MGG) [20], Central China (QC and LX) [20], South China (WL and LL) [20], Japanese cattle group (JB, JBR and JSH), European cattle group (HOL and BS), and Korean cattle (KN) (Figure 2; Table 4). At the c.*188G>A locus in AKIRIN2, the well-characterized A allele frequency in the JG and KN was obviously higher than the other cattle groups ( Fig.…”
Section: Statistical Comparations Of Allele Frequencies Among Six Catmentioning
confidence: 99%
See 1 more Smart Citation
“…To further analyze the distribution of the well-characterized allele of each SNP in the cattle populations based on the different genetic background, the MGC, MGG, QC, LX, WL and LL of this study as well as the JB, JBR, JSH, HOL, BS and KN [19,[21][22][23] were divided into six groups which including North China (MGC and MGG) [20], Central China (QC and LX) [20], South China (WL and LL) [20], Japanese cattle group (JB, JBR and JSH), European cattle group (HOL and BS), and Korean cattle (KN) (Figure 2; Table 4). At the c.*188G>A locus in AKIRIN2, the well-characterized A allele frequency in the JG and KN was obviously higher than the other cattle groups ( Fig.…”
Section: Statistical Comparations Of Allele Frequencies Among Six Catmentioning
confidence: 99%
“…Therefore, the objectives of this study reported herein were to: (1) perform association analyses between these SNPs in the AKIRIN2, TTN, EDG1 and MYBPC1 genes and growth-related traits in QC, (2) investigate the genetic diversity of these SNPs in three Chinese typical cattle groups (including QC, Mongolia cattle (MG), Luxi (LX), Wuling (WL) and Longlin (LL) cattle breeds), and (3) compare the frequencies of the well-characterized alleles of these SNPs in Chinese cattle breeds to those of JB, Japanese Brown (JBR), Japanese Short Horn (JSH), Holstein (HOL), Brown Swiss (BS) [21][22][23], and KN breeds [19].…”
Section: Introductionmentioning
confidence: 99%
“…Wagyu cattle breeds were regarded as Bos taurus type that carrying T allele, and the consequently on its inheritances (Casas et al, 2007;Van Eenennaam et al, 2007). This occurance may caused by strong selection in Wagyu breed for marbling traits as well as on alleles of other candidate genes associated with high marbling (Watanabe et al, 2011).…”
Section: Genetic Polymorphism Analysismentioning
confidence: 99%
“…In mammals, Akirin2 is considered to be closely related to innate immune response and embryonic development (Goto et al, 2008;Macqueen and Johnston, 2009;Beutler and Moresco, 2008). There is a body of recent evidence suggesting that Akirin2 plays a crucial role in skeletal myogenesis (Macqueen and Johnston, 2009;Macqueen et al, 2010;Chen et al, 2013), and the Akirin2 gene is regarded as a positional functional candidate for the gene responsible for marbling (Sasaki et al, 2009;Watanabe et al, 2011;Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%